System emerytalny w kraju karteli - przypadek Kolumbii - Poteraj, Jarosław (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The 1993 reform was the most important change, ordering many elements of Colombian retirement. Today, the Colombian pension system is characterized by parallel (pay-as-you-go and funded) schemes, which creates inefficiencies in administration because of its complexity and consequently increases systemic costs. A system that is formally defined as a two-pillar system is actually a three-pillar solution, based on the principle of competition between the components. Linking a minimum pension with a minimum wage is a significant source of ineffectiveness of the adopted solution. In international comparisons, there is also a lack of thinking about the potential equalization of the retirement age for women and men. Changes in recent years, especially the introduction of BEPS, Colombia Mayor and family pensions, are substantiated. Still, there is a lack of effective instruments in Colombia that radically increase the coverage of the pension system. In the paper the hypothesis that in a country with a large share of the shadow economy in the creation of GDP there are difficulties in increasing participation in the pension system, was confirmed
Keywords: retirement; pension systems; Colombia